Computational plasticity in powder forming processes - Khoei, Amir R.
The powder forming process is an extremely effective method of manufacturing structural metal components with high-dimensional accuracy on a mass production basis. The process is applicable to nearly all industry sectors. It offers competitive engineering solutions in terms of technical performance and manufacturing costs. For these reasons, powder metallurgy is developing faster than other metal forming technology. Computational Plasticity in Powder Forming Proceses takes a specific look at the application of computer-aided engineering in modern powder forming technologies, with particular at.